The stock market and cross-country differences in relative prices - Borja Larrain (Federal Reserve Bank of Boston, 2005)
This paper studies the impact of stock market development on cross country relative prices (the real exchange rate). A nonlinear relationship is uncovered in the cross section: prices and the stock market increase together in the beginning; then prices fall as the stock market continues to develop. In fact, among rich countries the relationship between prices and the stock market is negative. This result obtains after controlling for per capita income and for endogeneity issues by using legal origins. A small open economy model is presented to explain the connection between stock market development and relative prices: better investment opportunities increase consumption levels and the price of nontradable goods (income effect); but if stock market assets are less labor intensive than previous entrepreneurial technologies, prices can fall as the stock market grows because more labor is available for producing nontradables (substitution effect). This paper illustrates the connection of the stock market with goods and labor markets; it also has potential implications for the political economy of financial development. In a sideline contribution, it provides prices for entrepreneurial assets.
Keywords: F3; G0; 330